2018
DOI: 10.1111/evj.12995
|View full text |Cite
|
Sign up to set email alerts
|

Advanced mare age impairs the ability of in vitro‐matured oocytes to correctly align chromosomes on the metaphase plate

Abstract: Advanced mare age predisposes to chromosome misalignment on the metaphase II spindle of IVM oocytes. The compromised ability to correctly align chromosomes presumably predisposes to aneuploidy in resulting embryos and thereby contributes to the age-related decline in fertility and increased incidence of early pregnancy loss. The Summary is available in Portuguese - see Supporting Information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 26 publications
4
48
0
2
Order By: Relevance
“…Multivariable analysis has found the mare level factors of increasing age, one previous live foal and the presence of uterine cysts to be positively associated with EPL. Evidence suggests it is oocyte deficits rather than endometrial dysfunction which are the main contributors relating mare age to EPL [20,21,26,27]. Cytogenetic analysis to establish chromosomal aberrations would be beneficial to explore the pathophysiology behind oocyte-related failures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multivariable analysis has found the mare level factors of increasing age, one previous live foal and the presence of uterine cysts to be positively associated with EPL. Evidence suggests it is oocyte deficits rather than endometrial dysfunction which are the main contributors relating mare age to EPL [20,21,26,27]. Cytogenetic analysis to establish chromosomal aberrations would be beneficial to explore the pathophysiology behind oocyte-related failures.…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of chromosomal abnormalities to EPL in the mare is not currently known, although two chromosomal abnormalities have been demonstrated experimentally in equine embryos [24] and new methods to study conceptual material from clinically failed pregnancies are now available [25]. It is also plausible that EPL derived from oocyte defects could arise by mitochondrial defects or chromosome misalignment on the metaphase II spindle which have been shown to increase in aged mares [26,27]. These oocyte abnormalities are likely to also contribute to earlier pregnancy losses (prior to day 15) not assessed as part of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aged oocytes also display altered microtubule spindle alignment [57] and weakened centromere cohesion [58] resulting in increased risk of aneuploidy. In the mare, advancing maternal age significantly increases the risk of chromosome misalignment [19] and early pregnancy loss [7]. Therefore we proposed that advancing mare age would increase the risk of aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst an abnormal uterine environment, more prevalent in aged mares, is likely to be a contributing factor, experiments involving the transfer of embryos from young mares into old mares (and vice versa) have suggested that this is not the main age-related underlying cause [16]. Oocytes from aged mares are of lower quality compared with younger fertile mares [1719], indicating oocyte quality as a more likely risk factor for pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%